How Much Will Safe Sanitation for all Cost? Evidence from Five Cities - Delaire, Caroline; Peletz, Rachel; Haji, Salim (Environ. Sci. Technol., 2020)
: Global sustainable development goals call for universal access to safely managed sanitation by 2030. Here, we demonstrate methods to estimate the financial requirements for meeting this commitment in urban settings of low-income countries. Our methods considered two financial requirements: (i) the subsidies needed to bridge the gap between the willingness-to-pay of low-income households and actual market prices of toilets and emptying services and (ii) the amounts needed to expand the municipal waste management infrastructure for unserved populations. We applied our methods in five cities− Kisumu, Malindi, Nakuru in Kenya; Kumasi in Ghana; and Rangpur in Bangladesh and compared three to five sanitation approaches in each city. We collected detailed cost data on the sanitation infrastructure, products, and services from 76 key informants across the five cities, and we surveyed a total of 2381 low-income households to estimate willingness-to-pay. We found that the total financial requirements for achieving universal sanitation in the next 10 years and their breakdown between household subsidies and municipal infrastructure varied greatly between sanitation approaches. Across our study cities, sewerage was the costliest approach (total financial requirements of 16−24 USD/person/year), followed by container-based sanitation (10−17 USD/person/year), onsite sanitation (2−14 USD/person/year), and mini-sewers connecting several toilets to communal septic tanks (3−5 USD/person/year). Further applications of our methods can guide sanitation planning in other cities.
Keywords: Sanitation; Eloïse Charreyron; ACE: Energy and Environmental Sustainability; Ghana; Power; University of Energy & Natural Resources